2022
DOI: 10.1155/2022/7624578
|View full text |Cite
|
Sign up to set email alerts
|

Sports Training Strategies and Interactive Control Methods Based on Neural Network Models

Abstract: Sports training strategies should be combined with science and technology to design the most suitable coaching strategies for athletes. In the current 5G Internet of Everything, the collection of wireless sensors and the deep learning of neural networks provide a new direction for the formulation of sports training strategies, guiding sports strategies to be more effective and scientific. This article aims to study and formulate sports training strategies, through the empowerment of science and technology, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…The performance of the proposed correlation method is analyzed using experimental analysis using the data source in [32]. This data source analyzes the WS data from 9 sensors placed at different parts of a human body for its correlation.…”
Section: Resultsmentioning
confidence: 99%
“…The performance of the proposed correlation method is analyzed using experimental analysis using the data source in [32]. This data source analyzes the WS data from 9 sensors placed at different parts of a human body for its correlation.…”
Section: Resultsmentioning
confidence: 99%
“…During the actual operation of the system, various training parameters fluctuate randomly within a certain range; for example, the quality coefficient of pedaling power fluctuates around 0.9. e fluctuations of these training parameter indicators interact with each other, which is a fuzzy relationship with the training load level as the goal. e athlete adjusts the changes of relevant training parameters in a timely manner according to the feedback navigation instruction information to stabilize it within the area corresponding to the target load level [20]. When the fluctuations of various training parameters under a certain training load level gradually decrease and become stable, it means that the training level of the athlete's current load level has improved.…”
Section: End Submentioning
confidence: 99%
“…It implements the self-Modification diminishing algorithm, which was enhanced by the convolution's self-coding mechanism (SCM).In order to develop a modern health information network for sports medicine, the CNN makes the processing of complicated athletic health data simpler and completes a cloud-based circuit model. Study [17] suggested an interactive control approach for sports training that raises the standard for instruction using the deep fusion of data and increases human-machine interaction.The aggregation of wireless sensors and neural networks for deep learning techniques led to a current revolution in sports training methods. Theyallow for the development of more efficient and scientific sports methods.…”
Section: Related Workmentioning
confidence: 99%